Matematika 1: skripta - Sovič, Tina; Špacapan, Simon (2018)
Mathematics 1. Script Mathematics 1 is a study guide for students of Faculty of Civil Engineering, Transportation Engineering and Architecture of University of Maribor. The first part contains chapters on analysis, while the second part deals with algebraic topics. The first chapter introduces the concept of a sequence and describes some of its properties, like monotone, bounded and convergent sequence. Complex numbers and operations on them are presented in the second chapter. In the sequel we give a  list of elementary functions and their properties.  The infinitesimal calculus with a detailed explanation of a derivative and the anti-derivative of a function is also given, moreover several applications of these two concepts are shown. The first part concludes with a brief look  into functions of two variables. In the second part we introduce geometric vectors and operations between them, we  discuss lines and planes in the space. We conclude the script with matrices and operations on them, systems of linear equations, and the matrix of a linear mapping
Keywords: sequences; functions; derivative; integral; vectors; sistem of equations; matices